2018
DOI: 10.3390/met8080635
|View full text |Cite
|
Sign up to set email alerts
|

Study on Porous Mg-Zn-Zr ZK61 Alloys Produced by Laser Additive Manufacturing

Abstract: This study reports the effect of Zn contents on surface morphology, porosity, microstructure and mechanical properties of laser additive manufacturing (LAM) porous ZK61 alloys. The surface morphology and porosity of the LAMed porous ZK61 alloys depend on the laser energy input. With increasing Zn contents, the surface quality of porous Mg-Zn-Zr alloys became worse, the grains are obviously refined and the precipitated phases experienced successive transitions: MgZn → MgZn + Mg 7 Zn 3 → Mg 7 Zn 3 . The microhar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…But they did not study the effect of laser power on the internal pores of the samples. Zhang et al (2018) studied the effect of laser power and Zn content on porous Mg-Zn-Zr alloys. They found that excessive laser energy would make the surface morphology worse.…”
Section: Introductionmentioning
confidence: 99%
“…But they did not study the effect of laser power on the internal pores of the samples. Zhang et al (2018) studied the effect of laser power and Zn content on porous Mg-Zn-Zr alloys. They found that excessive laser energy would make the surface morphology worse.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the solid solution strengthening theory of Mg alloys, the lattice distortion caused by the solid solution of Zn limits the dislocation movement between the grains and boundaries (Shuai et al, 2017;Zhang et al, 2018). Zirconium is used as the most common grain refiner in Mg alloys that not contain Al, Mn, Si, Fe, Sn, Ni, Co and Sb (Ali et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…AZ91 [26] 104-167 1-1.2 WE43 [25] 238 1 ZK60 [30] 420-750 2-8 ZK30-xAl [31] 4004 Al(wt.%): 0-7 21.6 ± 2.6-7.3 ± 1.0 ZK61-xZn [42] 1146 Zn(wt.%): 5-30 1.1-6.1 Mg-9Al [32] 94-250 10-20 Mg [37] 60-120 5-20 Mg-2Ca [38] 1200 5 Mg-xSn [39] 107 Sn(wt.%): 0-7 5-25 Mg-3Zn-xDy [40] 360 Dy(wt.%): 0-5 6.4-18.1 AZ61 [41] 138-208 1.6-2.5 Mg-Gd-Zn-Zr [44] 27-267 1.3 ± 0.4-2.3 ± 1.0 Second, because of the "solute capture" effect caused by rapid solidification, the solid solution of the elements in the matrix was enhanced, so the microhardness increased. Al and Zn, as common alloying elements, were solid-solved into the magnesium alloy matrix.…”
Section: Alloymentioning
confidence: 99%